Does regulatory reform of cumulative voting promote a more balanced power distribution in the boardroom? - Chen, Yinghui; Du, Julan (Journal of Corporate Finance, 2020)
In the presence of dominant shareholders, it remains uncertain whether the introduction of cumulative voting (CV) in board elections can elevate board representation of non-controlling substantial shareholders and curb the expropriation of minority shareholders by dominant shareholders. With hand-collected director-level data, we conduct DID-style analysis of China's CV reform. We find that non-controlling substantial shareholders cooperated in voting to raise their board representation, and CV implementation curbed tunneling activities and enhanced firm value. The results are especially strong in a subsample of firms whose second largest shareholder has a sufficiently large ownership proportion to elect her/his favored candidates onto boards.